Severe hypoglycemia and hyperinsulinemia in falciparum malaria. - White, N; Warrell, D; Chanthavanich, P; Looareesuwan, S; Warrell, M; Krishna, S; Williamson, D; Turner, R (1983)
We studied the occurrence, clinical manifestations, and mechanism of hypoglycemia in patients with falciparum malaria in eastern Thailand. Hypoglycemia, which was often severe and recurrent, occurred in 17 patients, including 12 in a series of 151 patients with cerebral malaria. Thirty episodes were investigated. Plasma concentrations of insulin and C peptide were inappropriately high, and lactate and alanine concentrations were significantly higher than in patients with falciparum malaria who were normoglycemic (P less than 0.05). Sixteen patients had received quinine; plasma quinine and insulin concentrations were correlated at the time of hypoglycemia (P = 0.007). In seven healthy fasting volunteers intravenous quinine increased the mean plasma insulin concentration (+/- S.D.) from 8.9 +/- 3.1 to 17.1 +/- 8.4 mU per liter (P = 0.02) and reduced the mean plasma glucose concentration from 88 +/- 20 to 68 +/- 23 mg per deciliter (P = 0.002). Our observations indicate that in falciparum malaria quinine-induced insulin secretion may precipitate hypoglycemia, but other factors, including the large glucose requirements of the malaria parasites may also contribute. This important complication, associated with pregnancy and severe disease, must be excluded in all patients with falciparum malaria who have impaired or deteriorating consciousness.